Block-Parallel Chaotic Algorithms for Image Reconstruction - Gubareni, N.; Pleszczynski, M. (Электронное моделирование, 2009)
The paper is devoted to the elaboration and implementation of block-parallel asynchronous algorithms for computer tomography. The numerical reconstruction algorithms and numerical simulation results for a number of modeling objects and some particular systems of reconstruction are presented. Разработаны и выполнены блочно-параллельные алгоритмы компьютерной томографии.Представлены численные алгоритмы восстановления и результаты численного моделирования для ряда тестовых задач и некоторых частных случаев систем реконструкции сбора данных. Розроблено та виконано блочно-паралельні алгоритми комп’ютерної томографії. Наведено чисельні алгоритми відновлення та результати чисельного моделювання для тестових задач і деяких окремих випадків систем реконструкції збирання даних.